PEMENUHAN HAK ANAK KORBAN KEKERASAN SEKSUAL - Muhammad Alif Aulia Syahri (2023)
Cases of sexual violence are still a frequent case in Indonesia. Every year cases of child sexual violence increase, based on data from the Indonesian Child Protection Commission and the Ministry of Women's Empowerment and Child Protection is stated that the number of sexual violence whose victims are children has increased throughout 2019 to 2022. The research method used by the authors in this study is normative juridical. In this study, the author used a statutory approach (statue approach). The purpose of this research is to find out the extent of the implementation of the fulfillment of the rights of children victims of sexual violence. In the results of this study, the author found that cases of criminal acts of sexual violence against children increased every year, the authors also found that there are still many children who are victims of criminal acts of sexual violence still have not fulfilled the right of restitution and the right to rehabilitation as stated in the legislation due to the lack of clear arrangements or regulations for the application of restitution which causes law enforcement doubts in implementing it. The lack of Human Resources (HR) and budget is also an obstacle in fulfilling the right of children to rehabilitation to the maximum. Therefore, the arrangement for the application of restitution rights to victims must be reviewed more deeply so that the application of compensation to victims can be clear. In addition, the author expects society and the state to be present and participate in protecting children from sexual crimes that can occur at any time.